Comparison of the Efficacy of ECMO With or Without IABP in Patients With Cardiogenic Shock: A Meta-Analysis - Zeng, Ping; Yang, Chaojun; Chen, Jing; Fan, Zhixing; Cai, Wanyin; Huang, Yifan; Xiang, Zujin; Yang, Jun; Zhang, Jing; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Objective: Studies on extracorporeal membrane oxygenation (ECMO) with and without an intra-aortic balloon pump (IABP) for cardiogenic shock (CS) have been published, but there have been no meta-analyses that compare the efficacy of these two cardiac support methods. This meta-analysis evaluated the outcomes of these two different treatment measures. Methods: The PubMed, Embase, Cochrane Library, Web of Science and Clinical Trials databases were searched until March 2022. Studies that were related to ECMO with or without IABP in patients with CS were screened. Quality assessments were evaluated with the methodological index for nonrandomized studies (MINORS). The primary outcome was in-hospital survival, while the secondary outcomes included duration of ECMO, duration of ICU stay, infection/sepsis and bleeding. Revman 5.3 and STATA software were used for this meta-analysis. Results: In total, 9 manuscripts with 2,573 patients were included in the systematic review. CS patients who received ECMO in combination with IABP had significantly improved in-hospital survival compared with ECMO alone (OR=1.58, 95% CI=1.26-1.98, P<0.0001). However, there were no significant differences in the duration of ECMO (MD=0.36, 95% CI=-0.12-0.84, P=0.14), duration of ICU stay (MD=-1.95, 95% CI=-4.05-0.15, P=0.07), incidence of infection/sepsis (OR=1.0, 95% CI=0.58-1.72, P=1.0) or bleeding (OR=1.28, 95% CI=0.48-3.45, P=0.62) between the two groups in the patients with CS. Conclusion: ECMO combined with IABP can improve in-hospital survival more effectively than ECMO alone in patients with CS.